Solve for x
x=2
x=3
Graph
Share
Copied to clipboard
-81x^{2}+405x+250=736
Use the distributive property to multiply 9x+5 by -9x+50 and combine like terms.
-81x^{2}+405x+250-736=0
Subtract 736 from both sides.
-81x^{2}+405x-486=0
Subtract 736 from 250 to get -486.
x=\frac{-405±\sqrt{405^{2}-4\left(-81\right)\left(-486\right)}}{2\left(-81\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -81 for a, 405 for b, and -486 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-405±\sqrt{164025-4\left(-81\right)\left(-486\right)}}{2\left(-81\right)}
Square 405.
x=\frac{-405±\sqrt{164025+324\left(-486\right)}}{2\left(-81\right)}
Multiply -4 times -81.
x=\frac{-405±\sqrt{164025-157464}}{2\left(-81\right)}
Multiply 324 times -486.
x=\frac{-405±\sqrt{6561}}{2\left(-81\right)}
Add 164025 to -157464.
x=\frac{-405±81}{2\left(-81\right)}
Take the square root of 6561.
x=\frac{-405±81}{-162}
Multiply 2 times -81.
x=-\frac{324}{-162}
Now solve the equation x=\frac{-405±81}{-162} when ± is plus. Add -405 to 81.
x=2
Divide -324 by -162.
x=-\frac{486}{-162}
Now solve the equation x=\frac{-405±81}{-162} when ± is minus. Subtract 81 from -405.
x=3
Divide -486 by -162.
x=2 x=3
The equation is now solved.
-81x^{2}+405x+250=736
Use the distributive property to multiply 9x+5 by -9x+50 and combine like terms.
-81x^{2}+405x=736-250
Subtract 250 from both sides.
-81x^{2}+405x=486
Subtract 250 from 736 to get 486.
\frac{-81x^{2}+405x}{-81}=\frac{486}{-81}
Divide both sides by -81.
x^{2}+\frac{405}{-81}x=\frac{486}{-81}
Dividing by -81 undoes the multiplication by -81.
x^{2}-5x=\frac{486}{-81}
Divide 405 by -81.
x^{2}-5x=-6
Divide 486 by -81.
x^{2}-5x+\left(-\frac{5}{2}\right)^{2}=-6+\left(-\frac{5}{2}\right)^{2}
Divide -5, the coefficient of the x term, by 2 to get -\frac{5}{2}. Then add the square of -\frac{5}{2} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-5x+\frac{25}{4}=-6+\frac{25}{4}
Square -\frac{5}{2} by squaring both the numerator and the denominator of the fraction.
x^{2}-5x+\frac{25}{4}=\frac{1}{4}
Add -6 to \frac{25}{4}.
\left(x-\frac{5}{2}\right)^{2}=\frac{1}{4}
Factor x^{2}-5x+\frac{25}{4}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-\frac{5}{2}\right)^{2}}=\sqrt{\frac{1}{4}}
Take the square root of both sides of the equation.
x-\frac{5}{2}=\frac{1}{2} x-\frac{5}{2}=-\frac{1}{2}
Simplify.
x=3 x=2
Add \frac{5}{2} to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}